Inhibiting the Replication of the Dengue Virus Using In Vitro Influcid - O. V. Pyankov; S. A. Bodnev; A. V. Zaykovskaya; V. .. Kazakov; G. .. Schmidt (Антибиотики и Химиотерапия, 2020)
Given the lack of specific antiviral medicines to treat dengue fever, finding new medicinal products, including natural products, remains a highly pertinent goal. The objective of the study was to determine the antiviral activity of Influcid against dengue virus replication in vitro. Material and methods. Dengue virus DENV-2/RUS/TH-Novosibirsk02/2012 subtype 2 was used in this study. Vero cells were infected with dengue virus. Reduction of cytopathic effect and virus accumulation in culture fluid with the influence Influcid has been studied. Results and conclusions. The 50% inhibiting concentration of Influcid was determined as 58 mg/ml. The results obtained from these in vitro investigations show that Influcid is able to effectively inhibit dengue virus (subtype 2) replication in Vero cells. Since Influcid has a favorable benefit-risk profile it might be an option that can be used as treatment in addition to conventional medicine in patients suffering from dengue fever. The transferability of in vitro data to humans must show further investigations.